Isotretinoin and mental health in adolescents: Australian consensus. (28th November 2013) - Rowe, Casey; Spelman, Lynda; Oziemski, Margaret; Ryan, Alexander; Manoharan, Shobhan; Wilson, Perry; Daubney, Michael; Scott, James
Abstract Acne is a common condition among adolescents and has the potential to negatively impact on the psychological well‐being of those who suffer from it. In particular, depression and suicidal ideation are more common in adolescents with acne. Successful treatment of acne can improve the quality of life and reduce levels of anxiety and depression in these individuals. The current treatment of choice for severe or refractive acne is isotretinoin, a retinoid. While the possible causal association between isotretinoin and mental illness remains a controversial topic, a recent systematic review has presented evidence to support this relationship. In light of this evidence, a group of dermatologists and psychiatrists have collaborated to develop these recommendations to aid the safe prescribing of isotretinoin in adolescents. These clinical suggestions are aimed at practitioners in both disciplines to increase awareness of the current evidence in support of the association between isotretinoin and adolescent depression.